Analysis of the vibrational spectrum of the dihydrogen complex [W(CO)3(n2-H2)(Pisopropyl3)2]: A model for the vibrational spectrum of dihydrogen surface species - Parker, Stewart; Ramirez Cuesta, Anibal; Tomkinson, John; Mitchell, Philip (Ciencia)
We have investigated the vibrational spectrum of the dihydrogen complex [W(CO)3(n2-H2)(Pisopropyl3)2] with particular emphasis on the inelastic neutron scattering spectrum. Previous work treated the motion of the dihydrogen ligand as either the rotational transitions of dihydrogen in a deep attractive well or as the modes of a dihydrogen complex. We have shown that neither model on its own can account for the inelastic neutron scattering spectrum. The rotational model requires the addition of vibrations and the vibrational model, as calculated by density functional theory, requires the addition of a split ground state. We have also shown that there is significant mechanical coupling of the dihydrogen modes to those of the other ligands, especially the carbonyls. Simulation of the method used in the literature, shows that the most important result, the location of the torsional mode, is validated, but that the method is not reliable for higher energy modes. Assignments for the carbonyl modes and come of the skeletal modes are also given. The implications of the vibrational coupling for the use of the dihydrogen complexes as model compounds for surface species are considered.